Evaluating a monetary business cycle model with unemployment for the euro area - Nicolas Groshenny (National Bank of Belgium, 2009)
This paper estimates a medium-scale DSGE model with search unemployment by matching model and data spectra. Price mark-up shocks emerge as the main source of business-cycle fluctuations in the euro area. Key factors in the propagation of these disturbances are a high degree of inflation indexation and a persistent response of monetary policy to deviations from the inflation target
Keywords: E32; C51; C52; 330; DSGE models; business cycles; frequency-domain analysis; Dynamisches Gleichgewicht; Konjunkturtheorie; Geldtheorie; Suchtheorie; Eurozone; EU-Staaten